Placing Religious Social Action in the Multicultural City - Zavos, John (Journal of religion in Europe, 2018)
The cultural geographer Lily Kong argues that spatial analysis is vital for an interrogation of the contemporary complexity of religion. Building on this observation and broader theoretical understandings of the dynamics of space and place, this paper asks what happens when religious ideas and organisations are implicated in contemporary social action initiatives in ethnically diverse cities. Drawing on ethnographic data, it provides a detailed spatial analysis of a range of initiatives aimed at combatting food insecurity and other forms of deprivation in the city of Bradford in northern England. It examines how and why certain types of religious institution are dominant in the delivery of social action and explores the political significance of more fluid initiatives conducted by religiously diverse independent agents. The paper concludes that initiatives such as street kitchens and foodbanks are playing an important role in recalibrating the social location of religion in contemporary multicultural environments.